PENGARUH PRESTASI PRAKTIK KERJA INDUSTRI DAN HASIL BELAJAR KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHAAN SISWA KELAS XII AKUNTANSI SMK NEGERI 25 JAKARTA - DESTA AMBARSARI; ATI sumiati (Jurnal Ilmiah Econosains, 2016)
Abstract This research purpose is to find out the influence of industrial practice and entrepreneurship learning achievement to entrepreneurship interest, XII Accounting Class in SMK Negeri 25 Jakarta. This type of research is survey, with quantitative approach. Data recording, interview and questionnaire are research technique. Sampling technique used proportional random sampling. Total population in this study were 77 students with a sample of 64 students of XII accounting class in SMK Negeri 25 Jakarta. The results showed that: there is a significant positive influence of industrial practice and entrepreneurship learning achievement to entrepreneurship interest, XII Accounting Class in SMK Negeri 25 Jakarta. Thus if industrial practice and entrepreneurship learning achievement increases, the entrepreneurship interest will also increase. Keywords: industrial practice, entrepreneurship learning achievement, entrepreneurship interest.